The Role of Facial Fillers in Non-Surgical Rhinoplasty: A Systematic Review of Safety and Efficacy - Alhammadi, Majid; Almheiri, Ali Mohamed Alsari; Zaman, Khaled Al (American Journal of Health, Medicine and Nursing Practice, 2023)
Purpose: Facial fillers, also alluded to as dermal fillers, consist of injectable chemicals as portion of a minimally invasive strategy to incidentally enhance the aesthetic and appearance of facial highlights by correcting volumes. Non-surgical rhinoplasty, also called liquid rhinoplasty, includes the utilize of dermal fillers to improve the shape of the nose. Non-surgical rhinoplasty is picking up popularity over the surgical choice on account of its ease of application, cheaper cost, better safety profile, less adverse effects, and faster recuperation time. Nevertheless, with the complex nasal arterial vasculature and structure, complications have been detailed within the literature. In this review, we examine the distributed applications of facial fillers in non-surgical rhinoplasty and its viability and security profile as compared to the surgical alternative. Materials and Methods: A comprehensive literature review of articles on facial fillers in non-surgical rhinoplasty was performed. Search results were filtered to incorporate articles and studies that were distributed within the last five years, to increase the relevance of the results to current practices. Search results were then reviewed for significance to the utilize of facial or dermal fillers in non-surgical rhinoplasty only. Studies that detailed the role of face fillers in areas unrelated to rhinoplasty and nose defects were excluded. Findings: Seven articles met the inclusion criteria and discussed the role, security and viability of facial or dermal fillers in non-surgical rhinoplasty. Of these, three were designed to illustrate particular techniques embraced in non-surgical rhinoplasty as well as the common uses of diverse and common fillers. The remaining three reviewed the safety and viability of particular filler sorts: one article inspected the use of Hyaluronic corrosive based dermal fillers in non-surgical rhinoplasty, another reviewed the strategy of PMMA-collagen gel in non-surgical rhinoplasty absconds, and finally, a study analyzed the utilize of a hybrid nasal filler which combined agarose gel and hyaluronic corrosive. The remaining article from the literature reviewed a case from a patient who detailed persistent headache and migraine-like indications following non-surgical rhinoplasty. Conclusions: Facial fillers are compelling and safe options for patients who wish to rectify or enhance their nasal shape or form, without going for surgery. Although the results are not as permanent as with the surgical alternative, non-surgical rhinoplasty offers a better recovery time, and cheaper cost. Given the distinctive properties ascribed to each filler type, and the diverse cases of nasal deformities, the filler choice and area should be chosen on a patient-specific basis. Compared to surgical rhinoplasty, the complications and adverse occasions from the non-surgical injections are as a rule mild and self-limiting. While severe complications are uncommon, deep knowledge of the nasal anatomy and vasculature, as well as extensive training, stay the main ways to minimize their event and increase patient security and satisfaction. Implications to Theory, Practice and Policy: Severe complications are uncommon, deep knowledge of the nasal anatomy and vasculature, as well as extensive training, remain the main ways to minimize their event and increase patient safety and fulfillment. In any case, more studies are required to clearly establish the safety of dermal fillers, particularly in the long-term.